INVITED EDITORIAL Transdisciplinary Research Management: the Case For Specialised Skills - Jacques de Vos Malan (European Scientific Journal, ESJ, 2016)
An increasing proportion of research projects are interdisciplinary or even trans-disciplinary in nature, particularly in the case of research directed at addressing the ‘wicked’ problems that arise in public policy-making. Transdisciplinary work is complex, contestable, often culture-specific and messy. In these projects, the role of the research project manager, as facilitator and intermediary, often becomes crucial. An experienced transdisciplinary project manager will play an important function as a member of the leadership group, bridging and translating between the various disciplinary stakeholders, holding together the conceptual and practical elements of the project. This paper examines four of the specialised skills required of transdisciplinary project managers: the capacity for rigorous scoping; the development of a collaborative culture; familiarity with serious and pervasive ambiguity; and a clear understanding of target audiences. The findings draw on practical experience gained by the Australian Council of Learned Academies (ACOLA) research management team, through the delivery of the program Securing Australia’s Future, between 2012 and 2016.